Associations between diet and handgrip strength: a cross-sectional study from UK Biobank. (July 2020) - Gedmantaite, A.; Celis-Morales, C.A.; Ho, Frederick; Pell, JP; Ratkevicius, A.; Gray, S.R.
Highlights: Carbohydrate intake was negatively associated with grip strength in all particpants. Oily fish, retinol and magnesium intake were positively associated with grip strength in all particpants. In women only positive associations were observed between red meat, fruit and vegetables, vitamin E, iron, vitamin B12, folate and vitamin C and hand grip strength. In men only negative associations were seen between bread and processed meat and grip strength. Many aspects of diet are associated with muscle strength in older people and randomised controlled trials are needed to confirm causality of these observations. Abstract: The aim of the current study was to investigate the association between diet and handgrip strength. The current study included 68, 002 participants (age 63.8 ± 2.7 years, 50.3% women, 49.7% men) from UK Biobank. Diet and nutritional data (carotene, retinol, potassium, vitamin C, foliate, vitamin B12, vitamin B6, iron, vitamin E, calcium, magnesium, carbohydrates, protein, polyunsaturated fat, fat, starch and saturated fat) were collected and handgrip strength measured. Associations were compared, stratified by sex, using regression analyses, after adjustment for age, sex, month of assessment, ethnicity, deprivation index, height, comorbidities and total energy intake. The current data revealed negative associations between carbohydrate intake and handgrip strength as well as positive associations between oily fish, retinol and magnesium intake and grip strength in both sexes. In women, positive associations were observed between intake of red meat, fruit and vegetables, vitamin E, iron, vitamin B12, folate and vitamin C and hand grip strength. In men only negative associations were seen between bread and processed meat with grip strength. We have shown associations of several nutrients and food items with muscle strength and appropriately designed trials are needed to investigate whether these nutrients/food items may be beneficial in the maintenance of muscle during ageing.